Perception of Organizational Climate In Relation to Occupational Stress Among Teachers Working In Colleges of Education In Haryana: Exploring the Impact of Organizational Climate on Occupational Stress among Teachers in Haryana (Journal of Advances and Scholarly Researches in Allied Education, 2013)
The keystone in the educational edifice is doubtlessly the teacher. On him depends much more than any other, the progress and prosperity ofchildren? Nobody can effectively take his place or influence childrenin the manner and to the degree; it is possible, for him alone to do.  Itis strongly believed that to be a teacher is to be the member of a holy order.